Electrochemical Energy Generation by Reusing Domestic Gray Water - Rivera-Aquino, Hugo (2024)
This study explores the potential of converting domestic graywater into electrochemical energy as a sustainable energy solution amidst growing environmental concerns. Employing a custom-designed galvanic cell prototype, the research aims to transform the chemical energy in graywater into electrical energy through redox reactions, quantifying the electrical potential generated. Results demonstrate the prototype's success in generating an average no-load voltage of 5.1907 volts, effectively powering low-power devices like LEDs and validating the viability of greywater as an alternative energy source. However, the study acknowledges limitations such as the prototype's small scale and the potential impact of varied graywater compositions on energy efficiency, suggesting cautious application at larger scales. Future research directions include enhancing prototype efficiency and scalability, understanding the effects of different graywater compositions, and conducting long-term performance assessments. The study contributes to sustainable energy research by offering a novel approach to wastewater energy recovery, promoting environmental sustainability and efficient energy utilization.